Voluntary Assets and Income Declaration Scheme (VAIDS) and Company Income Tax in Nigeria: A Post-Mortem - Onwuka, Onwuka Okwara (Advances in Social Sciences Research Journal, 2019)
Abstract The contribution of taxation to any economy globally cannot be over emphasized. This research work is on Voluntary Assets and Income Declaration Scheme (VAIDS) and Company Income Tax (CIT): A Post-Mortem. The main objective of this study is to explore the impact of Voluntary Assets and Income Declaration Scheme on company income tax in Nigeria. Time series data were applied in carrying out this research work. Ordinary least square regression analysis was employed in this work with the use of STATA 13 package. The scope of the study is basically focused on the assessment and effect of voluntary assets and income declaration scheme on company income tax in Nigeria from June 2017 to March 2018 a period of 9 months but later extended to July 2018 by the Federal Government of Nigeria. This research focuses on a broad range of issues with the collection of a diversity of data in the field of VAIDS and company income. A literature review was used to determine the theoretical basis for research topic and prior research method conducted on various aspects of relating to VAIDS and company income tax. This work adopted the ex-post-facto research design. The findings reveal that Company Income Tax has an insignificant impact on VAIDS. The work recommends that the voluntary assets and income declaration scheme should be a permanent programme as a separate body should be set up to inspect and ensure the smooth running of the programme. Key words: VAIDS, Tax, Executive, Order, Income